TXT LINGO: a cross-sectional study on the impact on orthographic competence and performance - Sonia Sunny (Cogent Arts & Humanities, 2025)
Advancements in technology have ushered brevity in written communication. The increase in mobile phone users in India and the prevalence of text messaging has altered language conventions unprecedentedly. The present study focuses on analyzing the linguistic features of texting and its impact on the orthographic performance of tertiary-level learners. The writing patterns of Engineering students of two South Indian states were analyzed to investigate the texting patterns of students and their influence on students’ proficiency. A qualitative-driven mixed method was employed and a validated questionnaire was utilized for data collection. Findings revealed that the widespread integration of texting features and increased Texting frequency has a considerable impact on orthographic skills. The study recommends the integration of mobile learning and targeted writing practices to mitigate these challenges. To conclude, the frequency of texting has a negative impact on the Orthographic Competence and Performance of Engineering students at least in the Indian context.